HUBUNGAN PENGETAHUAN DENGAN KEJADIAN FLOUR ALBUS PADA WANITA USIA SUBUR DI WILAYAH PUSKESMAS LABUHAN RASOKI PADANGSIDIMPUAN TENGGARA - Juliana Lubis; Nurhanifah Siregar (Universitas Prima Indonesia, 2021)
Vaginal discharge is vaginal discharge that is not blood which is sometimes a clinical manifestation of various infections, malignancies, or benign reproductive tumors, which always wet and cause irritation, itching and reduce comfort in sex. This study aims to determine the relationship with the incidence of flour albus in women of childbearing age in the Labuhan Rasoki Public Health Center, Southeast Padangsidimpuan District. The design of this research is an analytic survey with a cross sectional approach. The sampling technique used the solvin formula and obtained 30 respondents. Analysis of the data with univariate and bivariate analysis with a significance level of 0.05. The results showed that there was a relationship between knowledge and the incidence of flour albus in women of childbearing age in the working area of ​​the Labuhan Rasoki Public Health Center, Padangsidimpuan, Southeast with p = 0.000 < p = 0.05. It is expected that respondents will increase their knowledge, especially about flour albus by actively participating in counseling and reading a lot from mass media and electronics.